Advantages And Disadvantages of Online Learning - Axmedova T.B; Kenjayeva N.D (Genius Journals, 2021)
Of the most oft-used terms after the pandemic is the term “new normal.” The new normal in education is the increased use of online learning tools. The COVID-19 pandemic has triggered new ways of learning. All around the world, educational institutions are looking toward online learning platforms to continue with the process of educating students. The new normal now is a transformed concept of education with online learning at the core of this transformation. Today, digital learning has emerged as a necessary resource for students and schools all over the world. For many educational institutes, this is an entirely new way of education that they have had to adopt. Online learning is now applicable not just to learn academics but it also extends to learning extracurricular activities for students as well. In recent months, the demand for online learning has risen significantly, and it will continue doing so in the future.
Keywords: online learning; technology; advantages and disadvantages of using online courses; efficiency